Modeling of Energy Requirement for Tillage Operations in a Sandy Loam Soil - Oyelade, O. A.; Oni, K. C. (Kathmandu University Journal of Science, Engineering and Technology, 2021)
Tillage, the mechanical manipulation of soil, demands a huge amount of energy in order to accomplish various tasks during field operation. Field tests and evaluation were conducted on 40 different tractor makes and models with matching implements on a sandy loam soil between 2005 and 2011 by the officials of the National Centre for Agricultural Mechanization (NCAM), Ilorin, Nigeria. Implements used for the trials were tractor mounted disc plough and off-set disc harrow. Each tractor was operated on an area of 0.25 hectare (25 m × 100 m) in a randomized complete block design (RCBD). Parameters measured include travel speed, actual and total time of operation, field efficiency, field capacities (effective and theoretical), depth and width of cut, average soil moisture content, average soil bulk density and average soil cone index in order to determine the energy requirement for each tractor-implement combination. Two models for predicting energy requirement during ploughing and harrowing operations were developed using 36 tractor test data. The multiple linear regression method was used for developing the two models. The remaining 4 tractor test data were used for cross-validation. The resulting model equations for ploughing and harrowing operations gave R-squared values of 0.859 and 0.776, respectively. Results obtained from the predicted energy requirement values when compared to that of the observed energy requirement values for both ploughing and harrowing operations gave correlation coefficient values of 0.927 and 0.881, respectively. Cross-validation results for the models developed for energy requirement during ploughing and harrowing operations gave test error values of 4672.3 J m-3 and 2721.1 J m-3, respectively.